Food processing handbook (Weinheim Wiley-VCH; [Chichester] [John Wiley, distributor], 2012)
"The second edition of the Food Processing Handbook presents a comprehensive review of technologies, procedures and innovations in food processing, stressing topics vital to the food industry today and pinpointing the trends in future research and development.

Focusing on the technology involved, this handbook describes the principles and the equipment used as well as the changes - physical, chemical, microbiological and organoleptic - that occur during food preservation. In so doing, the text covers in detail such techniques as post-harvest handling, thermal processing, evaporation and dehydration, freezing, irradiation, high-pressure processing, emerging technologies and packaging. Separation and conversion operations widely used in the food industry are also covered as are the processes of baking, extrusion and frying. In addition, it addresses current concerns about the safety of processed foods (including HACCP systems, traceability and hygienic design of plant) and control of food processes, as well as the impact of processing on the environment, water and waste treatment, lean manufacturing and the roles of nanotechnology and fermentation in food processing.

This two-volume set is a must-have for scientists and engineers involved in food manufacture, research and development in both industry and academia, as well as students of food-related topics at undergraduate and postgraduate levels.

From Reviews on the First Edition:
"This work should become a standard text for students of food technology, and is worthy of a place on the bookshelf of anybody involved in the production of foods. "Journal of Dairy Technology, August 2008

"This work will serve well as an excellent course resource or reference as it has well-written explanations for those new to the field and detailed equations for those needing greater depth." CHOICE, September 2006."--
Volume 2. Separations in food processing, Part 1 / Jame G. Brennan and Alistair S. Grandison; Separations in food processing, Part 2 : membrane processing, ion exchange, and electrodialysis / Michael J. Lewis and Alistair S.Grandison; Mixing, emulsification, and size reduction / James G. Brennan; Baking / Stanley P. Cauvain; Extrusion / Paul Ainsworth; Food deep-fat frying / Pedro Bouchon; Safety in food processing / Carol A. Wallace; Traceability in food processing and distribution / Christopher Knight; The hygienic design of food processing plant / Tony Hasting; Process control in food processing / Keshavan Niranjan, Araya Ahromrit, and Ashok S. Khare; Environmental aspects of food processing / Niharika Mishra ... [et al.]; Water and waste treatment / R. Andrew Wilbey; Process realisation [i.e., realization] / Kevan G. Leach; -- Microscopy techniques and image analysis for the quantitative evaluation of food microstructure / Marí de Jesús Perea-Flores ... [et al.]; Nanotechnology in the food sector / Christopher J. Kirby; Fermentation and the use of enzymes / Domitris Charalampopoulos; Index
UP System perpetual contents
Includes bibliographical references and index
Keywords: Food industry and trade